For this case we have the following equation:
[tex]\frac {1} {3} (x + 2) = \frac {2} {3} x + 4[/tex]
We apply distributive property on the left side of the equation:
[tex]\frac {1} {3} x + \frac {2} {3} = \frac {2} {3} x + 4[/tex]
Subtracting [tex]\frac {2} {3} x[/tex] from both sides of the equation:
[tex]\frac {1} {3} x- \frac {2} {3} x + \frac {2} {3} = 4\\- \frac {1} {3} x + \frac {2} {3} = 4[/tex]
Subtracting [tex]\frac {2} {3}[/tex]from both sides of the equation:
[tex]- \frac {1} {3} x = 4- \frac {2} {3}\\- \frac {1} {3} x = \frac {12-2} {3}\\- \frac {1} {3} x = \frac {10} {3}[/tex]
We multiply by 3 on both sides of the equation:
[tex]-x = \frac {10} {3} * 3\\-x = 10[/tex]
We multiply by -1 on both sides of the equation:
[tex]x = -10[/tex]
The solution of the equation is [tex]x = -10[/tex]
ANswer:
[tex]x = -10[/tex]